Menilik Kedudukan Hukum Waris Adat dalam Perspektif Hierarki Peraturan Perundang-undangan di Indonesia - Ardicha Caterine; Irbah Dhiaulhaq Salsabila (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Inheritance is part of civil law which is a vital part of family law. Inheritance conflicts still often occur in society. Indonesia consists of many tribes, customs and cultures, giving rise to a diversity of habits in living life. The habits of these groups of people become different points of view in determining legal standards in meeting all the needs of citizens. The kinship system has a major influence on inheritance from customary inheritance law. The kinship system is drawn along three lines, namely patrilineal, matrilineal and parental kinship. The hierarchy of statutory regulations is an order that determines the priority of use of existing legal regulations, the application of which varies from higher rules to lower rules. The research uses normative juridical methods which are carried out using three research materials. Primary materials are in the form of laws, secondary materials are books or journals, and tertiary materials are dictionaries or encyclopedias. Recognition of the existence of indigenous peoples in Indonesia is guaranteed in the constitution in Article 18B Paragraph (2). Customary law is not formally accommodated in Law Number 12 of 2011 but its application is the same as other statutory regulations which have binding legal force. Indonesia itself does not yet have a national inheritance law. Settlement of customary inheritance disputes in Indonesia is carried out by means of consensus resolution, resolution through customary institutions, and also resolution through the courts.